Accelerating cancer clinical trial recruitment through a financial reimbursement program integrated with patient navigation: an interrupted time series analysis. (December 2021) - Borno, Hala T.; Lin, Tracy Kuo; Zhang, Sylvia; Skafel, Andrea; Lalanne, Alyssa; Dornsife, Dana; Johnson, Robert; Spicer, Darcy; Small, Eric J.; Rhoads, Kim F.
Abstract: Background: Cancer treatment clinical trials face major challenges with patient recruitment. Strategies to address patient indirect costs associated with clinical trial participation may accelerate accrual overall. The current study examined the effect of the IMproving Patient Access to Clinical Trials (IMPACT) intervention on patient accrual to cancer treatment clinical trials at an academic medical center. The IMPACT intervention was an onsite patient navigator combined with a financial reimbursement program to address patient out of pocket costs and began on September 2018. Methods: This analysis measured frequency of patient enrollment in cancer treatment clinical trials and available cancer treatment clinical trials per month between January 1, 2016 and March 31, 2020. An interrupted time-series analysis (ITSA) was conducted to estimate changes in patient enrollment attributable to the IMPACT intervention. Results: During the study period, a mean of 69 patients enrolled in clinical trials per month (standard deviation (SD = 13), with 27 (SD = 7) in early phase vs 41 (SD = 12) in late phase clinical trials. The number of available clinical trials per month was 51 (SD = 2) overall, with 23 (SD = 1) in early phase vs 28 (SD = 1) in late phase context. A total of 3470 patients were enrolled in cancer treatment clinical trials during the evaluated time period, the majority of whom were men (1895, 55 %) and racially white (2267, 65 %). A statistically significant increase in the number of patients accrued as compared to the pre-intervention trend was observed; with approximately 1 additional patient accrued per month, with a larger effect on increase patient accrual for late phase clinical trials. Discussion: This study observed that the IMPACT intervention accelerated clinical trial recruitment, especially among late phase clinical trials. Future research will examine strategies to leverage this infrastructure to optimize recruitment among underrepresented patients. Policy summary: To improve clinical trial recruitment and ensure that trial results are representative of a diverse population it is critical for health policies consider patient out-of-pocket costs and potential reimbursement to alleviate financial burden associated with clinical trial participation. Furthermore, policies for facilitating clinical trial recruitment and participant retention should budget for and incorporate a navigation component to assist patients who may not be familiar with the healthcare system and available financial assistance.